The Correlation Between Teachers' Emotional Intelligence and Students' Learning Engagement in EFL Class - Satya Gumelar, Wahyu; Fitri Wulandari, Sri; Sucia Lestari, Tyara; Ruswandi, Riki (JEELS (Journal of English Education and Linguistics Studies), 2024)
The study aims to determine teachers’ emotional intelligence levels based on student perspectives and is supported by principal assessments. Besides, the research aims to identify the extent of learners’ engagement and assess if there is any connection between the emotional intelligence of teachers and learning engagement in EFL classes for students. The research population included students and principals of Madrasah Aliyah 5 Garut. For this study, a sample that involved 60 students was selected using disproportional stratified random sampling techniques from class X (n=30) and class XI (n=30). To collect data, the writers used a questionnaire that evaluated variables such as teachers’ emotional intelligence and students’ learning engagement in EFL classes. The descriptive analysis method was used to analyze data, while Pearson Product Moment with SPSS 22.0 for Windows was used for bivariate analysis. The research findings suggest that the emotional intelligence level of teachers is medium from the student's point of view with an average score of 10.07, while from the principal's assessment, it is high scoring an average of 12.2. There was a moderate level of students’ learning engagement, with a mean score of 12.46. Hypothesis analysis also found that there is a positive and significant relationship between teacher emotional intelligence and student learning engagement with a fairly strong correlation level. It can be concluded that teachers need to increase their emotional intelligence so that student learning engagement in EFL classes increases.